Social bonds as freedom : revisiting the dichotomy of the universal and the particular - Dumouchel, Paul, 1951-; Gotō, Reiko (Berghahn, 2015)
Central to discussions of multiculturalism and minority rights in modern liberal societies is the idea that the particular demands of minority groups contradict the requirements of equality, anonymity, and universality for citizenship and belonging. The contributors to this volume question the significance of this dichotomy between the universal and the particular, arguing that it reflects how the modern state has instituted the basic rights and obligations of its members and that these institutions are undergoing fundamental transformations under the pressure of globalization. They show that the social bonds uniting groups constitute the means of our freedom, rather than obstacles to achieving the universal.